P69 Examining strategies to increase knowledge mobilisation between public health england and key stakeholders: a mixed methods study. (2nd September 2017) - Johnson, R; Melendez-Torres, GJ; Currie, G; Bradley, P; Oyebode, O
Abstract : Background: Public Health England (PHE) is an executive agency, sponsored by the Department of Health, which aims to protect and improve the nation's health and wellbeing, and reduce health inequalities. PHE has a number of responsibilities relating to the collection, curation and sharing of research, data and other knowledge relevant to public health. The organisations key stakeholders include local authorities and clinical commissioning groups. PHE requested that an academic partner support the organisation to develop the organisation's knowledge mobilisation function. Methods: We conducted a sequential mixed methods study. 1. We performed a rapid evidence review to identify strategies which improve knowledge mobilisation; 2. We held a workshop for PHE staff during which we prioritised identified strategies using Delphi methods; 3. We conducted semi-structured interviews and a focus group with a range of PHE staff to discuss the relevance of identified strategies in context; 4. We integrated findings from all three sources using the Pillar Integration Process, a technique for analytical integration of mixed data. Results: We identified 13 relevant reviews/meta-reviews. 16 PHE staff attended the workshop. 18 PHE staff were involved in indepth qualitative work (8 semi-structured interviews, 1 focus group of 10 people). Of strategies identified in the literature, workshop participants agreed that some were already working well at PHE, and this was echoed in the qualitative findings. Existing strengths of the organisation are that it is large and trusted, with established local networks. Short term priorities included gaining better understanding of stakeholder needs and future challenges in order make best use of social marketing, tailoring and targeting, and also to reflect narratives that are of particular interest to both immediate and downstream users of PHE evidence (e.g. the Director of Public Health who directly accesses PHE evidence, but also the councillor who ultimately makes decisions based on this). A longer term priority was to develop methods of measuring and evaluating the use of PHE knowledge products. The importance of flexibility in approaches, harmonising rather than homogenising, was a strong theme arising from the qualitative work. Integrated findings highlight the legacy of multiple previous entities having come together to form PHE and the burgeoning identity of PHE as a knowledge brokering organisation. Conclusion: We have identified some priority actions for both the short and long-term to improve mobilisation of knowledge from PHE to key stakeholders. This project will inform the development of a knowledge mobilisation strategy at PHE.